The creative process of the Potehi puppet craftsman in Gudo Jombang - Hasprita Restiamangastuti Boru Mangunsong; Warih Handayaningrum (Pascasarjana Institut Seni Indonesia Surakarta, 2022)
Potehi Puppet is one of the traditional arts in the form of hand puppet performances from China that developed in Java, one of which was in Gudo, Jombang. This article aims to describe the creative process of the Potehi Puppet artist/maker in Gudo, which is correlated with family background and life experiences. The author finds a relationship between difficult life experiences and artistic family background with the artist's creative energy so that he can survive and continue to develop his work in difficult artistic conditions. This explains that difficult life experiences are also needed in creativity in terms of creativity theory and psychology. The method used is descriptive qualitative with interview data collection techniques with three artists/makers of Potehi Puppet in Gudo, namely Toni, Sony, and Samsul. Data analysis uses several main theoretical bases, namely Primadi Tabrani's creativity theory, and Graham Wallas's creativity, and research by Marie J.C. Forgeard is about taking advantage of adversity for increased creativity. This article can inspire artists, especially traditional artists, to take advantage of life's difficulties as a stepping stone to increasing creative energy, endurance, and creativity